2017
DOI: 10.3758/s13423-017-1393-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictive joint-action model: A hierarchical predictive approach to human cooperation

Abstract: Research in a number of related fields has recently begun to focus on the perceptual, cognitive, and motor workings of cooperative behavior. There appears to be enough coherence in these efforts to refer to the study of the mechanisms underlying human cooperative behavior as the field of joint-action (Knoblich, Butterfill, & Sebanz, 2011; Sebanz, Bekkering, & Knoblich, 2006). Yet, the development of theory in this field has not kept pace with the proliferation of research findings. We propose a hierarchical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 104 publications
(154 reference statements)
3
54
1
Order By: Relevance
“…In general, the ability to perform complementary actions in joint tasks and to imitate other actors is particularly advanced in humans, and is developed early in childhood. In line with our findings, a large body of evidence suggests that pairs of humans involved in joint action have internal models and expectations about the consequences of their own actions and about the actions undertaken by their interaction partner [33][34][35][36][37][38][39] . Quantitative models of sensorimotor interactions have so far also focused on the two-player scenario within a game-theoretic setup 18,19,40 .…”
Section: Discussionsupporting
confidence: 89%
“…In general, the ability to perform complementary actions in joint tasks and to imitate other actors is particularly advanced in humans, and is developed early in childhood. In line with our findings, a large body of evidence suggests that pairs of humans involved in joint action have internal models and expectations about the consequences of their own actions and about the actions undertaken by their interaction partner [33][34][35][36][37][38][39] . Quantitative models of sensorimotor interactions have so far also focused on the two-player scenario within a game-theoretic setup 18,19,40 .…”
Section: Discussionsupporting
confidence: 89%
“…For instance, past studies (Sato and Yasuda, 2005;Farrer et al, 2008) observed agency can be misattributed to an external source when the outcome of an action is incongruent with own predicted sensory outcome, and attributing the motion to an external source. In reverse, the central nervous system can distinguish self-action and external sources through learning (Synofzik et al, 2006;Novembre et al, 2012;Pesquita et al, 2017). The monitoring of the sensory-motor error in regard with expected outcome may thus be linked to SoA (Bellebaum et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Enactive and embodied approaches to cognition are becoming increasingly interested in the affective dimension of human experience (Varela and Depraz, 2005;Colombetti, 2007Colombetti, , 2014Colombetti and Thompson, 2008;Di Paolo and De Jaegher, 2015;Gallagher and Varga, 2015;Gallagher and Allen, 2016;Scorolli, 2019). Consistently, this issue has been addressed in empirical research, which is paying growing attention to the affective quality of social contexts by addressing motor simulations (Bastiaansen et al, 2009;Kuhbandner et al, 2010), joint actions (Godman, 2013;Pesquita et al, 2018), emotional disorders (Gjelsvik et al, 2018), and body psychotherapy (Röhricht et al, 2014).…”
Section: Introductionmentioning
confidence: 99%